Diseño y simulación de un agitador de chocolate de 30 litros de capacidad con control de temparatura - Tutalchá Acosta, Jorge Luis (2016)
The work that the reader has available, was developed in order to study the heat transfer from a heating and mixing tank of small-scale chocolate. This project was proposed by an artisan chocolate maker from the parish Pomasqui. He has the potential to increase its current production volume, but for this he needs the most suitable tools. Note that the development of such ideas promotes a chain of events, which give some advantages to the whide society and not only to the authors, one of these events is the creation of more job creation and the economic development. During its development, several alternatives to solve the problem of the temperature distribution within the system were tested. first it was studied by an analytical approach in order to obtain a mathematical model of the entire process. The analytical solution was complicated to obtain. For this reason it was decided to analyze the system from the perspective of the numeric method. The structural design of the machine was another important point in this thises. The initial design idea was about two types of energy sources to perform its function: first the flames of a burner and depending on the economy of the person It was the cause of the issue, stop the burner and heat pass to feed the tank with water vapor flows.